2011
DOI: 10.1186/alzrt74
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction - the beginning of the end in Alzheimer's disease? Separate and synergistic modes of tau and amyloid-β toxicity

Abstract: The pathology of Alzheimer's disease (AD) is characterized by amyloid plaques (aggregates of amyloid-β (Aβ)) and neurofibrillary tangles (aggregates of tau) and is accompanied by mitochondrial dysfunction, but the mechanisms underlying this dysfunction are poorly understood. In this review, we discuss the critical role of mitochondria and the close inter-relationship of this organelle with the two main pathological features in the pathogenic process underlying AD. Moreover, we summarize evidence from AD post-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 69 publications
(97 reference statements)
3
114
0
3
Order By: Relevance
“…A mass spectrometric analysis of the brain proteins from these mice revealed mainly a deregulation of mitochondrial respiratory chain complex components (including complex V), antioxidant enzymes, and synaptic protein space (11). The reduction in mitochondrial complex V levels in the P301L tau mice that was revealed using proteomics was also confirmed as decreased in human P301L FTDP-17 (FTD with parkinsonism linked to chromosome 17) brains. The functional analysis demonstrated age-related mitochondrial dysfunction, together with reduced NADHubiquinone oxidoreductase (complex I) activity as well as age-related impaired mitochondrial respiration and ATP synthesis in pR5 mice model.…”
Section: Separate Modes Of Ab and Tau Toxicity On Mitochondriamentioning
confidence: 82%
See 1 more Smart Citation
“…A mass spectrometric analysis of the brain proteins from these mice revealed mainly a deregulation of mitochondrial respiratory chain complex components (including complex V), antioxidant enzymes, and synaptic protein space (11). The reduction in mitochondrial complex V levels in the P301L tau mice that was revealed using proteomics was also confirmed as decreased in human P301L FTDP-17 (FTD with parkinsonism linked to chromosome 17) brains. The functional analysis demonstrated age-related mitochondrial dysfunction, together with reduced NADHubiquinone oxidoreductase (complex I) activity as well as age-related impaired mitochondrial respiration and ATP synthesis in pR5 mice model.…”
Section: Separate Modes Of Ab and Tau Toxicity On Mitochondriamentioning
confidence: 82%
“…Within the past years, several mouse models have been developed that reproduce the aging process and diverse aspects of AD. These models help in understanding the age-related pathogenic mechanisms that lead to mitochondrial failure in AD, and in particular the interplay of AD-related cellular modifications within this process (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are summarized in recent review articles, therefore suggesting that Aβ is responsible for the induction of mitochondrial dysfunction typically observed in AD ( Fig. 1) [10][11][12].…”
Section: Introductionmentioning
confidence: 76%
“…Several studies have identified structural and functional mitochondrial abnormalities in hippocampal neurones of AD patients compared with age-and sex-matched controls [213][214][215][216]. Such abnormalities include a significant reduction in mitochondrial numbers and exaggerated levels of oxidised mitochondrial DNA (mtDNA) and nitrated proteins in the cytoplasm in a pattern suggestive of impaired mitophagy or fission dynamics [215][216][217]. These mitochondrial abnormalities are accompanied by oxidative damage marked by 8-hydroxyguanosine and nitrotyrosine, indicating that the mitochondria are damaged by ROS and RNS during disease progression [213,218,219].…”
Section: Oxidative Stress and The Development Of Mitochondrial Dysfunmentioning
confidence: 99%